Ազգային ինքնության արտացոլումը Սիմեոն Պղնձահանեցու մատենագրական ժառանգության մեջ - Բոզոյան, Ազատ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Материалом для данной публикации послужили памятные записи (колофоны), связанные с литературной деятельностью переводчика Симеона из Плндзаханка. В XIII в. им были переведены с грузинского языка на армянский труды Прокла Диадоха, Иоанна Синаита и др. The material for the present publication is the colophon records on the literary activity of the translator Simeon of Plndzahank’. In the XIII century, he translated the works of Proclus Diadochus, John Sinaiticus, etc. from Georgian into Armenian.
Keywords: Պատմություն